Educational practices in physical education and sports education for secondary education under the new approach - Bekhtaoui, Djamal; Mokrani, Djamal (Journal of Human Sciences, 2023)
We aim through this research to analyze Pedagogical practices in the study of physical and sports education for secondary education in light of the new approach, where the researchers used the descriptive approach to suit this study, and l he study was carried out on a statistical society represented in a sample of 206 teachers of physical education and sports. The workers of some Algerian high schools use a network of questionnaires and the researchers managed to tell the Pedagogical practices in the study of physical and sports education for secondary education in the light of the new approach based on the educational objectives and procedures and assessment, and from there, physical and sports education plays a leading role in the development of teacher performance, including the reform of education systems during the reform of teaching materials.